Diversity And Distribution Of Trichoptera (INSECTA) Larvae In Selected Rivers Of Royal Belum State Park, Gerik, Perak With References To Habitat Preference And Diel Periodicity - Rusli, Siti Mariam Zhafarina (2011)
A relatively rich community of immature Trichoptera (8624) from 16 families and 27 genera were collected from four rivers; Kejar, Mes, Tan Hain and Ruok, in Royal Belum State Park, Perak, Malaysia. Trichopteran assemblages were diverse (I-D = 0.83 - 0.85) but unevenly scattered in all rivers (E1/D, 0.29-0.36). Their densities ranged between 6.48 larvae/m2 in Ruok River and 10.08 larvae/m2 in Tan Hain River. Among Trichoptera families, Hydropsychidae and Philopotamidae were the most dominant. Chimarra (Philopotamidae) was very important in all rivers. Lepidostoma was very important (Important Species Index, ISI) in rivers other than Ruok River, while Ceratopsyche was prominent in Mes and Tan Hain rivers. Although measured physico-chemical parameters had a weak influence on the abundance of Trichoptera larvae, the CCA biplot showed variation in responses of Trichoptera larvae to the physico-chemical parameters of the water. Neophylax, Hydromanicus, Marilia and Lepidostoma were positively influenced by COD, pH, TDS, conductivity and river width. Agapetus, Ecnomus, Glossosoma, Ganonema and Ceratopsyche associated with escalating DO and NH3-N, while Setodes and Stenopsyche preferred less shaded habitats.